The effectiveness of applying the Hanifida method to students' ability to memorize the Qur'an by controlling their initial abilities - Fitriyani Nurfitroh; Rumbang Sirojudin; Deni Iriyadi; Ilzamudin; Rifyal Ahmad Lugowi; Muhammad Abdan Syakurof (At Turots: Jurnal Pendidikan Islam, 2025)
Memorizing the Quran is crucial for developing students' character and spirituality, yet many students struggle to maintain memorization. This study aims to test the effectiveness of the Hanifida method on memorizing Surah Ar-Rahman and the participants' initial ability to acquire the required. The Hanifida method is a brain-based learning approach that integrates visualization, number association, storyboarding, and systematic repetition. This study was quantitative with a quasi-experimental non-equivalent control group design. The sample consisted of two groups of students at the Al-Qur'an Az Zahra Islamic Boarding School and the Nurul Hidayah Mandalawangi Islamic Boarding School. The experimental group used the Hanifida method and the control group used traditional methods. The researcher used pretest and posttest observations. Data analyzed from both groups showed that the experimental group experienced significant improvements in memorization skills compared to the control group. Furthermore, the Hanifida method has the ability to increase students' reading motivation and active participation. The study shows that the Hanifida method can be used as a fun, structured, and appropriate learning method that reminds students of memorization failures by observing and repeating verses from Surah Ar-Rahman.